Students’Ability in Reading Comperhension of the Scond Grade at SMP 13 Berau 2018/2019 - Sarlina Sarlina; Nurbianta Nurbianta (Universitas PGRI Semarang, 2018)
The problem formulation of this research are: What is the students’ ability in reading comprehension . Design of this research was quasi experimental research, by conducted Pretest-treatments-posttest procedures. While the subject is 27 students of junior high school in the school year 2017/2018. The object the researchis the student’ ability in reading comprehension. To collect the data, the writer uses some tecniques suchas test and document. Data processing in this research is divided into five phases: validity, reability, Scoring the test, ranking and mean,median and mode then all the data are analyzed quantitavely The result finding of this research was the mean score students' reading test is 77.41, the value of median is 65, and the value of mode is 80.The performance on posttest show that the students’ ability in reading comprehension is outgrowth, the students obtained positive progress in learning reading skill.